2022
DOI: 10.1021/acs.macromol.1c02542
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ring Rigidity on the Statics and Dynamics of Linear Catenanes

Abstract: We used molecular dynamics simulations to investigate the statics and dynamics of poly­[n]­catenanes for different bending rigidities of the constituent rings. We show that stiffer rings yield catenanes with more extended and, at the same time, more flexible backbones. The softening of the backbone reflects the decreasing steric interactions of catenated rings as their shape becomes more oblate due to increased rigidity. The internal dynamics of catenanes is affected too. Going from flexible to rigid rings cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 56 publications
2
20
0
Order By: Relevance
“…We also note that a similarly short correlation range was previously reported for the influence of mechanical bonding on the statics and dynamics of free catenanes. 15,24,25 The data of Figure 6 thus show that the nematic ordering of rings with even and odd indices persists in channels and is largest at the onset of strong confinement (D ∼ 9σ). At these channel widths, concatenated rings themselves start to elongate, their shape changing from quasi-planar to uniaxially anisotropic, and the principal direction of the gyration tensor is increasingly aligned to the channel axis (Supporting Information).…”
Section: ■ Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…We also note that a similarly short correlation range was previously reported for the influence of mechanical bonding on the statics and dynamics of free catenanes. 15,24,25 The data of Figure 6 thus show that the nematic ordering of rings with even and odd indices persists in channels and is largest at the onset of strong confinement (D ∼ 9σ). At these channel widths, concatenated rings themselves start to elongate, their shape changing from quasi-planar to uniaxially anisotropic, and the principal direction of the gyration tensor is increasingly aligned to the channel axis (Supporting Information).…”
Section: ■ Resultsmentioning
confidence: 84%
“…In addition, different models have shown that, at small scales, the Rouse-like relaxation modes seen in linear polymers are replaced by slower ones in mechanically bonded chains of rings. 11,15,23,24 These ongoing efforts have significantly advanced our understanding of isolated and interacting catenanes in bulk. 15,16,22−27 However, except for Hopf links, 28,29 no characterization exists yet of catenanes in spatial confinement, despite it being a natural avenue considering the body of knowledge available for conventional polymers in channels and slits.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Varying the stiffness also affects properties of rings in films, 70,71 melts 56 or catenanes. 72 To understand such complex, many-body effects, we have to at first understand the simpler two-body problem.…”
Section: Introductionmentioning
confidence: 99%